The performance of loan disbursement for micro financing at Bank Kerjasama Rakyat Batu Pahat / Siti Nurfaezah Mardi - Mardi, Siti Nurfaezah (2012)
The purpose of microfinance is to help the lower income group to get funds for their business activities and at the same time can improve their lives. In Malaysia, microfinance scheme enable micro entrepreneurs to expand existing economic activities and consequently in scaling up their income. Bank Kerjasama Rakyat Berhad is the one of the financial institution that provide micro finance scheme which is Microfinance MUsK-I (Modal Untuk Usahawan Koperasi). Every month headquarter of Bank Rakyat give the budget of loan that should be achieved. Regarding of this achievement the researcher in this study want to evaluate the performance of file disbursement for micro finance scheme of Bank Kerjasama Rakyat Berhad and this research has been done in Bank Rakyat Batu Pahat Branches that focus Micro finance enterprises in Batu Pahat area. Since it was introduced on 2008 until 2011 by Bank Kerjasama Rakyat, Batu Pahat the record of loan approved show that the Bank has disbursement about RM4,820,100 total amount of loan under Microfinance MUsk-I (Modal Untuk Usahawan Koperasi) that the total of loan include for the retail, service and manufacture sector which is not achieve the target by Bank. The maximum amount the Bank should achieve is RM2 million per year but every year the Bank do not achieve the benchmark. From the record show that 45 percent of the disbursement comes from retail sector, 34 percent of this amount is disbursed from services sector and another 21 percent with RM1,029,800 is for manufacture sector.